البنية الحجاجيّة في القرآن الكريم في قصّتي يوسف وموسى ـ عليهما السّلام ـ دراسة مقارنة - باي، مارية, قدوري، وفاء (جامعة الوادي University of Eloued, 2019)
هدفت هذه الدّراسة الموسومة بالبنية الحجاجيّة في القرآن الكريم في قصّتي يوسف وموسى – عليهما السّلام- دراسة مقارنة إلى دراسة ظاهرة الحجاج في النّص القرآني من منطلقاته المنطقيّة والبلاغيّة؛ لإظهار أهم آليات النظريّة الحجاجيّة وتقنياتها عند بيرلمان وتيتكا الّتي تصل بالنّص التّخاطبي لأعلى درجات التّفاعل والتّواصل بين متكلّمه ومتلقّيه، لتحقيق متلازمة الإفهام الّتي تصل به للإقناع، ليكون وسيلة لإذعان المتلقي وتسليمه لما يطرح عليه، ولتحقيق هذه الغاية قسّمنا الدّراسة إلى أربعة فصول، حيث تطرّقنا في الفصل الأوّل إلى تعريف الحجاج لغة واصطلاحا، وتتبعنا المسار التّاريخي لنظريّة الحجاج عند العرب والغربيّين، ثمّ قمنا بمقابلة مفهوم الحجاج بغيره من المفاهيم الّتي تلابسه وتتداخل معه اتفاقا واختلافا كالجدل والخطابة والبرهان والإقناع والسّرد ثمّ عرّجنا إلى طبيعة الخطاب الحجاجي وأهم سماته الّتي تميّزه عن باقي الخطابات الأخرى، أمّا في الفصول الأخرى حاولنا التّأسيس للدّراسة التّطبيقيّة على قصّتي يوسف و موسى-عليهما السّلام-،حيث قمنا في الفصل الثّاني بتتبّع ورصد الحجج والآليات الشّبه منطقيّة في كلّ من القصّتين ثمّ مقارنتهما ومدى قابليتهما للإقناع، وخصّصنا الفصل الثّالث للحجج المؤسّسة على بنية الواقع في كلّ من القصّتين ومقارنتهما وما حملته من قوّة إقناعيّة لأكثر العقول إلحادًا و عنادًا، و أثرها في تغيير مفاهيمهم العقائديّة، ورابع فصول الدّراسة تناولنا فيه أقوى الحجج الّتي حملت سمة الجماليّة والإبتكاريّة وهي الحجج المؤسّسة لبنية الواقع، والّتي من خلالها تتحقّق إثارة الإقناع والامتاع ليدرك المتلقي سموّ هذا الخطاب القرآني الحجاجي نظمًا ومعنى، وأنهينا الدّراسة بخاتمة ذكرنا فيها أهم ما توصلنا إليه من نتائج في هذا البحث. This study, which is related to the structure of the pilgrims in the Holy Quran in the stories of Joseph and Moses - peace be upon them - a comparative study to study the phenomenon of pilgrims in the Quranic text from its logical and rhetorical points of view; to show the most important mechanisms of the theory of Pilgrim and its techniques at Perlman and Titka, which reach the highest level of interaction and communication between the speaker In order to achieve the syndrome of understanding that reach the persuasion, to be a means of submission and submission of the recipient to what is raised, and to this end we divided the study into four chapters, where we discussed in the first chapter to the definition of pilgrims language and terminology, We discussed the concept of pilgrims with other concepts that they wear and overlap with them, such as argument, rhetoric, proof, persuasion and narration, and then we have become accustomed to the nature of the Hajjian discourse and its most important features that distinguish it from the rest of the other speeches. Applied to the stories of Joseph and Moses - peace be upon them - where we have in the second chapter to track and monitor the arguments and mechanisms quasi-logical in each of the two stories and then compared and their ability to persuade, and devoted the third chapter of the arguments based on the Bani In the two stories and comparing them and the power of persuasion of the most stubborn minds and stubbornness, and their impact in changing their doctrinal concepts, and the four chapters of the study dealt with the strongest arguments that carried the aesthetic and innovative arguments are the foundation of the structure of reality, through which to achieve the excitement of persuasion and pleasure to realize The recipient of this Qur'anic discourse is a system and meaning, and we concluded the study with a conclusion in which we mentioned the most important findings of this research.
Keywords: البنية – الحجاج – الآليات – الإقناع; Structure - Pilgrims - Mechanisms – Persuasion.